2015
DOI: 10.1080/02640414.2015.1052746
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine ingestion enhances perceptual responses during intermittent exercise in female team-game players

Abstract: We examined the influence of caffeine supplementation on cognitive performance and perceptual responses in female team-game players taking low-dose monophasic oral contraceptives of the same hormonal composition. Ten females (24 ± 4 years; 59.7 ± 3.5 kg body mass; 2-6 training sessions per week) took part in a randomised, double-blind, placebo-controlled crossover-design trial. A 90-min intermittent treadmill-running protocol was completed 60 min following ingestion of a capsule containing either 6 mg • kg(-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 48 publications
2
42
0
2
Order By: Relevance
“…In resistance exercise, the effects are less clear, although supplementation appears to increase peak strength of the knee extensors [3] and time to fatigue in submaximal isometric contractions [4, 5]. Supplementation has also been shown to decrease feelings of fatigue and promote mood and perceptual responses during exercise [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In resistance exercise, the effects are less clear, although supplementation appears to increase peak strength of the knee extensors [3] and time to fatigue in submaximal isometric contractions [4, 5]. Supplementation has also been shown to decrease feelings of fatigue and promote mood and perceptual responses during exercise [6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…Caffeine supplementation also decreased fatigue and promoted feelings of pleasure during intermittent exercise in this cohort [7]. While it is likely that caffeine supplementation and OCS-associated metabolism have important implications for performance in women undertaking high-impact sport, this information is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies had been shown the effectiveness of caffeine on improve endurance exercise [6][7][8][9]17]. Interestingly, current study showed that using coffee espresso (high dos coffee) on hour prior the exercise could significantly improve the VO2max compared with without coffee condition.…”
Section: Discussionmentioning
confidence: 63%
“…Numerous studies have shown that caffeine can act as an ergo-genic aid, in long-term exercise [5][6][7][8][9]. Caffeine's primary ergo-genic mode of action is on the CNS [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation